Ecological studies of Falkland Islands' waterfowl - Weller, Milton W (Wildfowl, 1972)
A variety of marine and freshwater habitats occur on the cold-temperate Falkland Islands. Although thirteen species of waterfowl have nested on the islands, only eleven are seen regularly. Intensive study of habitat selection, food utilization and reproductive behaviour of five species and general observations on six others revealed that waterfowl species were well-distributed with little overlap in food use even in the same habitat. Herbivorous species constituted 65% of the total waterfowl observed and different species fed on marine algae (Kelp Geese Chlophaga hybrida malvinarum), upland grasses and forbs (Upland Geese Chlophaga picta leucoptera and Ruddy-headed Geese Chlophaga rubidiceps) or freshwater submergents (Black-necked Swan Cygnus melanocoryphus and Chiloe Wigeon Anas sibilatrix). Two carnivores utilizing marine inshore and tidal zones were next in abundance; Falkland Flightless Steamer Ducks Tachyeres brachypterus fed on bottom organisms by diving and Crested Ducks Lophonetta s. specularioides fed in the gravel and silt on smaller invertebrates. Three species of dabbling ducks were more social and omnivorous but mainly utilized the abundant invertebrates of freshwater ponds. Although some inter-specific competition was noted at edges of territories or feeding sites, species generally are segregated in different niches. Reproductive behaviour patterns are influenced by a climate moderated by the sea and, although seasonal breeding is common in Upland Geese and Kelp Geese, nests of Crested Ducks and Chilean Teal Anas f. flavirostris have been recorded in all months of the year. Growth rate of young is slow by northern hemisphere standards, and territorial behaviour is more pronounced. Upland Geese have become a dominant species because development of grazing lands provides choice habitat. In spite of competition with sheep for grass, protection is essential for all species of sheldgeese because they are important components of a unique avifauna significant to scientists and attractive to tourists. Although generally like the waterfowl fauna of Tierra del Fuego, that of the Falkland Islands is unique in one species (Falkland Flightless Steamer Duck) and two endemic subspecies (Upland Goose and Kelp Goose).